Characterization of a Magnetorheological Fluid Damper Applied to Semi-Active Engine Mounting System / M. Hafiz Harun...[et al.] - Harun*, M. Hafiz; Azhari, Muhamad Azwar; Yunos, R.; Mat Yamin, A. K.; Sariman, M. Z. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This study is to propose a hysteresis damper model that can be integrated with the vehicle control system. A prototype of magnetorheological for engine mounting has been designed and tested to realize the objective of this study. The experimental on the prototype of the magnetorheological damper for engine mounts has been conducted in order to investigate the hysteresis of this damper. From the experiment, the results are evaluated in terms of damping force versus piston displacement and also the damping force versus piston velocity. It is significantly shows that the proposed model satisfy the non-linear hysteresis behavior of the MR damper in the form of force-velocity and force-displacement characteristics.